Precipitation, Temperature, and Population Structure Influence Genetic Diversity of Oakleaf Hydrangea Throughout Its Native Range - Andrew Sherwood; Lisa W. Alexander; Matthew D. Clark; Xingbo Wu; Stan C. Hokanson (Journal of the American Society for Horticultural Science, 2023)
Oakleaf hydrangea (Hydrangea quercifolia) is an understory shrub native to the southeastern United States. The species occupies a relatively small native range, and little is known about its demography, genetic diversity, or needs for conservation. Samples were collected from 188 plants in 73 locations throughout the species range and were genotyped using genotyping by sequencing. A structure analysis identified six genetic clusters that are geographically defined. Although these clusters are weakly differentiated, each has unique alleles. An environmental association analysis revealed that environmental variables explain 11.3% of genetic diversity, and population structure explains 13.5%. Further, 231 putative adaptive alleles were identified, most of which are correlated with precipitation-related variables, indicating that precipitation has an impact on genetic diversity in H. quercifolia. Many historically documented populations were found to be either extirpated or at risk of extirpation. The genetic clusters on the southern extent of the species range are relatively small and contain putative adaptive alleles at relatively high frequencies. These results highlight the importance of preserving representative germplasm from throughout the species range.